Implementacion de la responsabilidad social empresarial en las empresas mineras socialmente responsables desde la óptica del Tribunal Constitucional - Damiàn Roque, Roxana Esther (2019)
This thesis that develops the theme of "IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY IN SOCIALLY RESPONSIBLE MINING COMPANIES FROM THE OPTICS OF THE CONSTITUTIONAL COURT", arises as a result of the alarming journalistic notes of environmental damages and social conflicts generated by a mining company ; moreover, it is worrisome that, in many of the cases, they are companies that have implemented Corporate Social Responsibility; therefore, the need arises to investigate what is the status of the implementation of Corporate Social Responsibility in these companies, since they are the ones that, due to their commitment, must show a behavior to prevent environmental damage and social conflicts; as it has been established in the Jurisdictional Plenary Of the Constitutional Court in the EXP. No. 0001-2012-PI / TC. In the first part, the methodological framework is developed, through which the problematic and hypothesis developed in the present thesis has been reached; where, methods and materials have also been developed. In the methodology we used: The Analytical-Synthetic Method, to examine the main studies, reports, resolutions, normativity and jurisprudence on Corporate Social Responsibility in order to extract the important points of this thesis; Inductive-Deductive, through the study of jurisprudence, doctrine, regulations and legislation on Corporate Social Responsibility to arrive at conclusions; qualitative, to verify if the implementation of Corporate Social Responsibility is achieving the prevention of environmental damage and social conflicts; hermeneutic-dialectic, to extract the most important points of the development of Corporate Social Responsibility (jurisprudence, doctrine, regulations and legislation) and analyze the status of the implementation of Corporate Social Responsibility in socially responsible mining companies; and Dogmatic, to analyze the concepts, regulations, laws Esta obra ha sido publicada bajo la licencia Creative Commons Reconocimiento-No Comercial-Compartir bajola misma licencia 2.5 Perú. and theories related to Corporate Social Responsibility. The techniques used for the following investigation are: The technique of the transfer where the technique of documentary collection is used, to compile the main jurisprudences of the Constitutional Court that has developed the subject of the Corporate Social Responsibility, the normativity and legislation on the Corporate Social esponsibility , dogmatics, reports, resolutions; of signing, to obtain copies and summary of texts, regulations consulted; and of archives, to search among the resolutions of the Agency of Evaluation and Environmental Enforcement and of the Supervisory Body of the vestment in Energy and Mining, the reports of social conflicts of the ombudsman's office, risprudence of the Constitutional Court that has resolved on the subject of Corporate Social Responsibility, and books. The materials used are: The jurisprudence of the Constitutional Court that has resolved on the subject of Corporate Social Responsibility; the resolutions of the Supervisory Body for Investment in Energy and Mining (period 2011-2018) and the Agency for Environmental Assessment and Control (period 2012-2018), on the infractions of socially responsible mining companies; the reports of social conflicts of the ombudsman's office - adjunct for the prevention of social conflicts and governability (period 2012-2018); the national legislation that develops the topic of Corporate Social Responsibility; specialized magazines on the subject and finally the comparative rmativity on Corporate Social Responsibility. In the second part, in order to make a rigorous legal analysis on the subject addressed, the following four sub-themes have been developed in the theoretical framework: Corporate Social Responsibility, Socially Responsible Enterprise, Corporate Social Responsibility in Peruvian law, and the Court Constitutional and its Jurisdictional Plenary. In the third part, the analysis of a practical case is carried out: The Jurisdictional Plenary Session of the Constitutional Court in the EXP. No. 0001-2012-PI / TC, which has developed the topic of Corporate Social Responsibility. Analyzing, mainly, how it has been established that socially responsible mining companies should establish mechanisms to prevent environmental damage and social conflicts. In the fourth part, the development of the research is carried out, where the results were given, the discussion of results and conclusions of the present investigation, to finally give recommendations, which allow to investigate more about the topic of the present thesis; achieving that, the behavior of mining companies considered socially responsible, is consistent with the true nature of Corporate Social Responsibility, which in the field of law serves as a mechanism of protection of rights and is in accordance with the provisions of the Political Constitution of Peru.